Compliance charts to guide non-complex small artery stenting: validation by quantitative coronary angiography. Issue 1 (31st May 2013) - Chacko, Yohan; Haladyn, J Kimberly; Smith, Debbie M; Lim, Richard
Abstract : Objective: To determine whether stent sizing derived from manufacturers' compliance charts provides a reasonable in vivo estimate of final minimum lumen diameter (MLD) when compared with quantitative coronary angiography (QCA). Design: Single-centre measurement comparison study. Setting: Tertiary referral university hospital. Patients: Fifty cases receiving a single stent for non-complex de novo stenosis were randomly selected from the percutaneous coronary intervention database of our high-volume centre. Restenosis, stent thrombosis, bifurcational disease, rotablation, left main or graft stenting, intravascular ultrasound or kissing balloon inflations were exclusion criteria. Main outcome measures: Equality and limits of agreement (LOA) between compliance chart and QCA measurements of final MLD, especially focusing on patients with small stents<3 mm. The paired t test and Bland-Altman plots were used to compare measurements. Results: There was no significant difference between compliance chart-derived and QCA final MLD (n=50; mean −0.034 mm, SD 0.35, 95% CI −0.132 to +0.064; p=0.49), with reasonable Bland-Altman LOA between the two methods of assessing final MLD in the overall group (LOA −0.72 to +0.66 mm), as well as in the group of particular interest with Derived final MLD <3 mm (n=30; mean 0.019 mm, SD 0.27, 95% CI −0.082 to +0.119; p=0.71; LOA −0.52 to +0.56 mm). Conclusions: Compliance charts provide an acceptable estimate of final MLD and are a reasonable guide to sizing during non-complex stenting, especially in small vessels <3 mm.